The impact of error management atmosphere, organizational support, and self-efficacy on employee innovation: The roles of work passion and risk-taking trait - Yingjian Wang; Vesarach Aumeboonsuke; Jiafu Su (Environment and Social Psychology, 2025)
This paper takes error management atmosphere perception, perceived organizational support, and creative self-efficacy as independent variables, employees’ working passion as the mediating variable, risk-taking trait as the moderating variable, and employee innovation behavior as the dependent variable. It explores the relationships among error management atmosphere perception, perceived organizational support, creative self-efficacy, employees’ working passion, risk-taking trait, and employee innovation behavior. This study, integrating social cognition theory and creativity component theory, systematically explored the connections among various variables. The research indicates that enterprises should have a good atmosphere for error management, and at the same time, they should provide employees with sufficient organizational support. Only in this way can they continuously stimulate the innovative vitality of employees. It provides important insights for enterprise management practices, namely, creating a positive atmosphere of error management is a key way to stimulate employees’ innovative potential and enhance the organizational innovation ability.